The farnesyltransferase inhibitor L744,832 reduces hypoxia in tumors expressing activated H-ras. - Cohen-Jonathan, E; Evans, S; Koch, C; Muschel, R; Mckenna, W; Wu, J; Bernhard, E (2001)
Many tumors contain extensive regions of hypoxia. Because hypoxic cells are markedly more resistant to killing by radiation, repeated attempts have been made to improve the oxygenation of tumors to enhance radiotherapy. We have studied the oxygenation of tumor xenografts in nude mice after treatment with the farnesyltransferase inhibitor L744,832. Hypoxia was assessed by measuring the binding of the hypoxic cell marker pentafluorinated 2-nitroimidazole. We show that xenografts from two tumor cell lines with mutations in H-ras had markedly improved oxygenation after farnesyltransferase treatment. In contrast, xenografts from two tumors without ras mutations had equivalent hypoxia regardless of treatment. The effect on tumor oxygenation could be detected at 3 days and remained after 7 days of treatment. These results indicate that treatment with farnesyltransferase inhibitors can alter the oxygenation of certain tumors and suggest that such treatment might be useful in the radiosensitization of these tumors.